Analysis of Students’ Errors in Working on Number Theory Questions (21st century Skills) - Margaretha Madha Melissa; Cyrenia Novella Krisnamurti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to describe students’ mistakes in solving number theory’s problem. In this study, error analysis, especially on the topic of Diophantine equations and Chinese remainder theorem. This type of research is qualitative research. The subjects of this study were 46 students of mathematics education at Sanata Dharma University. The data collection technique used a test. The data were analyzed to determine errors in doing number theory problems using the type of error according to Newman. According to Newman, five types of errors are reading, comprehension, transformation, process skill, and encoding errors. The conclusion of this study showed that the most errors made were related to process skill errors and transformation errors, while only a few experienced comprehension and encoding errors. None of the students made reading error.This shows that students already understand the meaning of the problem, but when changing and looking for solutions to problems an error occurs. The factors that may cause this error are a lack of understanding of the concept of the Diophantine equations and Chinese remainder theorem, as well as a lack of problem practice.